High affinity promoter binding of STOP1 is essential for early expression of novel aluminum-induced resistance genes GDH1 and GDH2 in Arabidopsis. (22nd January 2021) - Tokizawa, Mutsutomo; Enomoto, Takuo; Ito, Hiroki; Wu, Liujie; Kobayashi, Yuriko; Mora-Macías, Javier; Armenta-Medina, Dagoberto; Iuchi, Satoshi; Kobayashi, Masatomo; Nomoto, Mika; Tada, Yasuomi; Fujita, Miki; et al.
Abstract: Malate efflux from roots, which is regulated by the transcription factor STOP1 (SENSITIVE-TO-PROTON-RHIZOTOXICITY1) and mediates aluminum-induced expression of ALUMINUM-ACTIVATED-MALATE-TRANSPORTER1 ( AtALMT1 ), is critical for aluminum resistance in Arabidopsis thaliana . Several studies showed that AtALMT1 expression in roots is rapidly observed in response to aluminum; this early induction is an important mechanism to immediately protect roots from aluminum toxicity. Identifying the molecular mechanisms that underlie rapid aluminum resistance responses should lead to a better understanding of plant aluminum sensing and signal transduction mechanisms. In this study, we observed that GFP-tagged STOP1 proteins accumulated in the nucleus soon after aluminum treatment. The rapid aluminum-induced STOP1-nuclear localization and AtALMT1 induction were detected in the presence of a protein synthesis inhibitor, suggesting that post-translational regulation is involved in these events. STOP1 also regulated rapid aluminum-induced expression for other genes that carry a functional/high-affinity STOP1-binding site in their promoter, including STOP2, GLUTAMATE-DEHYDROGENASE1 and 2 ( GDH1 and 2 ). However STOP1 did not regulate Al resistance genes which have no functional STOP1-binding site such as ALUMINUM-SENSITIVE3, suggesting that the binding of STOP1 in the promoter is essential for early induction. Finally, we report that GDH1 and 2 which are targets of STOP1, are novel aluminum-resistance genes in Arabidopsis. Abstract : STOP1 nuclear-localization and its high affinity binding to target gene promoters are essential for early aluminum-induced gene expression, with GDH1/2 being novel Arabidopsis Al-tolerance genes.